Karakteristik Morfologi Kambing Marica yang Dipelihara di Luar Habitatnya - Rosdiana Ngitung; Mushawwir Tayyeb; Irma Suryani Idris (Seminar Nasional LP2M UNM, 2019)
Abstract. This research is a descriptive study that aims to determine the morphological characteristics of Marica goats. That are kept outside the habitat. Observation of morphological characteristics, using 2 goats (1 male and 1 female). This research was conducted at the Biology Experiment Garden in Makassar State University, which lasted for 8 months. The results obtained by Marica Goat have a relatively small body dimensions, upright ears and relatively small short, short and small horns and look agile and aggressive Keywords: Marica Goat, morphological characteristics